L’identité francophone, la francophonie et la canadianité multiculturelle contemporaine : vers un renouvellement des formes de solitude ? - Aurélien Yannic (Anglophonia)
In the second half of the XXth century, the identity and the collective representation that the Canadian Federation had of itself as a social and national community was completely reshaped. First the period of the French Canada had to be repudiated. Then it was the whole Eurocentric construction, grounded on the theory of the two founding people, which was dismissed. Eventually Canada asserted its collective identity in the 1980s as a multicultural American society.In this context, one may wonder what the place and influence of French speaking Canadians can be today, confronted as they are with the increasingly organised claims of Québec and the overwhelming pressure of an American-ness modelled on the example given by the USA.We propose to confront in the following pages the various ways in which this question spells itself: Will Francophonie be displaced by the larger concept of Canadian-ness spawned by multicultural politics, or is it compatible with it? And is it possible to hold with Paul Martin that Canada is the first post-modern state in history?